Polar regions. - Parker, Steve (Laguna Hills, CA : QEB pub, 2008)
"Describes the land and ocean habitats of the polar regions, and how animals adapt to living in these cold ecosystems"--Provided by publisher.
Includes index. "Discover life in the coldest places"--Cover.
Keywords: Ecology --Polar regions --Juvenile literature; Polar regions --Juvenile literature